أثر الاستثمار في التعليم العالي على النمو الاقتصادي-دراسة حالة الجزائر للفترة 1971-2020 - نيس, سعيدة (جامعة الوادي - University of Eloued, 2023)
تهدف هذه الورقة البحثية الى دراسة العلاقة السبيبة بين التعليم العالي والنمو الاقتصادي في الجزائر خلال الفترة 1971-2020، وذلك من خلال تحديد أثر الاستثمار في التعليم العالي على النمو الاقتصادي باستخدام المنهجين الوصفي والتحليلي، والاستعانة بأداة القياس الاقتصادي لتقدير العلاقة بين المتغيرين في المديين الطويل والقصير، وقد استعملنا لتحقيق ذلك منهجية الانحدار الذاتي للفجوات الزمنية المتباطئة. توصلت الدراسة الى نتيجة لا تتوافق مع النظرية الاقتصادية والدراسات التجريبية التي أجريت على مختلف الاقتصاديات خاصة تلك التي أجريت على البلدان المتقدمة حيث يبين نموذج التقدير وجود علاقة سببية سلبية ومعنوية بين المتغيرين في المدى الطويل، يظهر ذلك من خلال معلمة راس المال البشري السالبة (-1,38) التي تدل على أن زيادة مخزون راس المال البشري المتراكم من خلال التعليم العالي بـ 1٪ يؤدي إلى انخفاض النمو الاقتصادي بـ 1,38٪. This research paper aims to study the causative relationship between higher education and economic growth in Algeria during the period 1971-2020, by determining the impact of investment in higher education on economic growth, using the descriptive and analytical approaches, and econometrics tool to estimate the relationship between the two variables in the long and short term. To achieve this, we use the Auto Regressive Distributed lag methodology. This study reached a conclusion that does not agree with economic theory and experimental studies conducted on various economics, specially conducted on developed countries, where the estimation model shows the existence of a negative and significant causal relationship between the two variables in the long run, and this shown through the negative human capital parameter (-1,38), which indicates that increasing the stock of human capital accumulated trough higher education by ٪ leads to a decrease economic growth by 1,38٪
مقال
Keywords: النم ; الاقتصادي ; اقتصاد التربية ; التعليم العالي ; راس المال البشري; economic growth; education economic; higher education; human capital